2022
DOI: 10.1080/22221751.2021.2022440
|View full text |Cite
|
Sign up to set email alerts
|

Omicron variant showed lower neutralizing sensitivity than other SARS-CoV-2 variants to immune sera elicited by vaccines after boost

Abstract: The emerging new VOC B.1.1.529 (Omicron) variant has raised serious concerns due to multiple mutations, reported significant immune escape, and unprecedented rapid spreading speed. Currently, studies describing the neutralization ability of different homologous and heterologous booster vaccination against Omicron are still lacking. In this study, we explored the immunogenicity of COVID-19 breakthrough patients, BBIBP-CorV homologous booster group and BBIBP-CorV/ZF2001 heterologous booster group against SARS-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
323
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 338 publications
(372 citation statements)
references
References 16 publications
32
323
1
1
Order By: Relevance
“…Besides, the protection against infection of Omicron from symptomatic disease at 25 weeks after 2-dose vaccination was suggested to be less than 10% in the UK 22 . Similar to these preliminary real-world data, here we reported that a markedly reduced neutralizing activity against Omicron variant in the convalescent and two-dose BBIBP-CorV vaccination group, which is also confirmed by others 23,24 . However, the good news is that after two doses of inactivated vaccines as the “priming” shot, a third homologous inactivated vaccine booster or a heterologous protein subunit vaccine booster could elevate neutralization titer against Omicron.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Besides, the protection against infection of Omicron from symptomatic disease at 25 weeks after 2-dose vaccination was suggested to be less than 10% in the UK 22 . Similar to these preliminary real-world data, here we reported that a markedly reduced neutralizing activity against Omicron variant in the convalescent and two-dose BBIBP-CorV vaccination group, which is also confirmed by others 23,24 . However, the good news is that after two doses of inactivated vaccines as the “priming” shot, a third homologous inactivated vaccine booster or a heterologous protein subunit vaccine booster could elevate neutralization titer against Omicron.…”
Section: Discussionsupporting
confidence: 91%
“…However, the good news is that after two doses of inactivated vaccines as the “priming” shot, a third homologous inactivated vaccine booster or a heterologous protein subunit vaccine booster could elevate neutralization titer against Omicron. Our results are quite comparable to studies on the same inactivated vaccine 23 or other vaccines 25 , and again supported by the real-world data showing a third dose booster vaccination provides increased protection against Omicron 26 .…”
Section: Discussionsupporting
confidence: 88%
“…This variant contains >30 spike protein amino acid mutations that possibly are associated with increased transmissibility, severity, and capacity for immune escape [ [4] , [5] , [6] ]. It has been found that Omicron variant may lead to more significant escape from immune protection elicited by previous SARS-CoV-2 infection and perhaps even by existing Coronavirus disease 2019 (COVID-19) vaccines [ [7] , [8] , [9] , [10] ]. Thus, Omicron was designated as variant of concern (VOC), by the World Health Organization (WHO) on November 26th, 2021 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Besides the homologous boosting, heterologous booster strategy has also attracted great concerns, and several clinical trials and cohort studies have shown that the heterologous primebooster vaccination was immunologically superior than homologous counterparts. [8][9][10][11][12] However, the immunogenicity of the heterologous prime-booster vaccination with the inactivated vaccine and the recombinant subunit vaccine was evaluated recently only in a small size of samples, and the neutralizing antibodies against live SARS-CoV-2 were not detected in the study. 11,12 Till now, it is still lacking a large-scale clinical trial to evaluate the immunogenicity of heterologous boost with the recombinant subunit vaccine in individuals primed with the inactivated vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] However, the immunogenicity of the heterologous prime-booster vaccination with the inactivated vaccine and the recombinant subunit vaccine was evaluated recently only in a small size of samples, and the neutralizing antibodies against live SARS-CoV-2 were not detected in the study. 11,12 Till now, it is still lacking a large-scale clinical trial to evaluate the immunogenicity of heterologous boost with the recombinant subunit vaccine in individuals primed with the inactivated vaccine. Besides that, the neutralization ability of heterologous booster vaccination against the newly epidemic Omicron variant also needs to be tested.…”
Section: Introductionmentioning
confidence: 99%